Penetapan Kadar Flavonoid Daun Waltheria Indica yang Hidup di Daerah Gambut, Kalimantan Selatan - Pertiwi Awilda; Choirul Choirul; Bawaihi Bawaihi; Kunti Nastiti (An-Najat, 2024)
Waltheria indica is a shrub that can grow in various soil locations. This plant has a variety of chemical content ranging from terpenoids, alkaloids, flavonoids and terpenoids. This plant has benefits including fever, cough, skin diseases, rheumatism, chest tightness, anorexia, wounds, jaundice, boils and overcoming infertility problems. This study aims to determine the total flavonoid content of the stem-leaf extract of the sepat fern. The method used in this study is Colorimetry using AlCl3 reagent which is used to determine the total flavonoid content. Based on the research conducted and obtained the total flavonoid content obtained from the sepat fern extract is equivalent to 3.425% w/w quercetin equivalent.